ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL BANGUN DATAR PADA MATA KULIAH GEOMETRI (Jurnal Pelangi : Research of Education and Development, 2022)
This study aims to describe student errors in solving flat-shaped questions. The research subjects were students of the Mathematics Education study program, STKIP PGRI, West Sumatra. This type of research is a qualitative descriptive that describes the types of errors and the level of student response in solving geometry problems on flat-shaped material. The results showed the types of errors including conceptual errors, data errors, language interpretation errors, technical errors and conclusions drawing errors